Is smart beta investing profitable? evidence from the Nordic stock market - Silvasti, Veikkopekka; Grobys, Klaus; Äijö, Janne (Routledge, Taylor & Francis Group, 2020)
This study examines the profitability of the mixing and integrating approach for constructing multi-factor smart beta portfolios. While most studies explore this issue in a U.S. market setting, this is the first study that exclusively focus on the Nordic equity market, which exhibits some unique and stylized features as recently highlighted in the literature. Our findings indicate first strong evidence for return variations for sorting stocks on value-, momentum-, and ex-ante beta-signals. Surprisingly, variations in payoffs are not only small stock phenomena in the Nordic equity markets. While the current literature does not yet agree on a consensus, our study supports the literature documenting the superiority of the integrating approach. Our results challenge the efficient market hypothesis in a market environment offering a high-level of information-flow-efficiency.
Keywords: Smart beta; multi-factor investing; value; momentum; low beta; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|